Review of Sleep Disorders and Therapeutic Approaches in Patients With Autism Spectrum Disorder and Rett Syndrome - Katelyn Bricker; Bradley V. Vaughn (Sleep Medicine Research)
Sleep complaints are frequent in children with autism spectrum disorder and Rett Syndrome and sleep itself may influence further neurodevelopment in these disorders. This comprehensive review attempts to explore the connection between sleep disorders and brain development in children facing autism spectrum disorder and Rett Syndrome. We will evaluate the underlying neurobiological mechanisms and potential interventions.